Mobile Cloud Computing (MCC): A Survey of Privacy, Security and their Impact on Social Life of Users - Syed Zohaib Hassan; Muhammad Awais Bawazir; Ayesha Irshad; Kalsoom Ayaz; Ayesh Aslam; Jamaluddin Mir (Journal of Management Practices, Humanities and Social Sciences, 2022)
A foremost debated area in the IT world is Mobile Cloud Computing (MCC) which merges cloud computing and mobile computing; MCC is a prospective technology of mobile services that have been inaugurated together with the fast development in mobile applications and cloud computing technology. MCC is in the early phase of development, so it is essential to have in-depth knowledge of the technology to identify future research. Cloud computing has seen exceptional advancement in the past couple of years regarding its turn of application and development. Thus, development and research in cloud computing are scaling in a positive direction because of the increasing demand for cloud computing. On the other hand, no one is concerned about its effect on mental health. People are more concerned about the privacy, access, and security of their data over the cloud. Users are not aware of the data stored in cloud technology. Therefore, end users are always worried about the security and privacy of personal data. When cloud base services are used, users have mental stress because of the unknown place of the data storage. Consistent use of cloud-based services creates a sense of anxiety among users that are more particular about data privacy. The present article gives a transitory explanation of cloud computing and mobile computing. Applications such as M-healthcare, M-commerce, and M-gaming have been discussed to debate potential applications for mobile cloud computing.